Analysis of Alfred Scuzt's Motivation Theory in Boyan Muslim Philanthropic Motivation in Malaysia and Singapore for Bawean Community Economy - Barakah, Ainun; Halim, Abdul (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2023)
The focus of this research is the study of the phenomenon of motivation for sending philanthropy from Orang Boyan in Malaysia and Singapore to Bawean Island. This research confirms that the relationship between the Boyan people and the Bawean community is the driving force for philanthropic actions on Bawean Island. This research answers the question of what motivates Boyan Muslims to do philanthropy for the Bawean people. This research is socio-economic based research using descriptive qualitative methods. To find out this, the author uses Schuzt's motivation theory which says that in his actions, humans have causes and goals. In this study it is known that the causes that motivate philanthropic actions are factors of economic difficulties, gratitude, primordial and socio-religious practices, which aim to improve the economy, return favors, advance the area of origin and obtain religious values.